2018
DOI: 10.1007/s10554-018-1353-x
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial deformation as a potent predictor for paroxysmal atrial fibrillation in patients with end-stage renal disease

Abstract: It is widely known that various factors contribute to left atrial (LA) mechanical dysfunction in patients with end stage renal disease (ESRD). However, the connection between atrial dysfunction and arrhythmic events such as paroxysmal atrial fibrillation (PAF), in this group of patients, remains unclear. The purpose of our study was to evaluate prospectively the association between LA deformation indices and PAF in ESRD patients. 79 patients (41 men, mean age 57 ± 17) with ESRD and preserved left ventricular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…25 Papadopoulos et al demonstrated in 79 ESRD patients that LA reservoir strain predicted paroxysmal atrial fibrillation. 26 A recent study of patients with pre-dialysis chronic kidney disease (CKD) Stages 3/4 by Gan et al showed that LA reservoir strain was a very good predictor F I G U R E 3 Subgroup analyses for the primary outcome showed that albumin, dichotomized as the median serum albumin (3.6 g/dl), was a significant interaction term for the association of left atrial (LA) reservoir strain with the primary outcome (AUC 0.84) for MACE and overall death, and its association with the composite outcome was significant after adjustment for comorbidities and echocardiographic parameters. 27 To our knowledge, we are the first to characterize LA volume, LA reservoir strain, LA conduit strain, and LA booster strain in an ESRD cohort with adjudicated MACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Papadopoulos et al demonstrated in 79 ESRD patients that LA reservoir strain predicted paroxysmal atrial fibrillation. 26 A recent study of patients with pre-dialysis chronic kidney disease (CKD) Stages 3/4 by Gan et al showed that LA reservoir strain was a very good predictor F I G U R E 3 Subgroup analyses for the primary outcome showed that albumin, dichotomized as the median serum albumin (3.6 g/dl), was a significant interaction term for the association of left atrial (LA) reservoir strain with the primary outcome (AUC 0.84) for MACE and overall death, and its association with the composite outcome was significant after adjustment for comorbidities and echocardiographic parameters. 27 To our knowledge, we are the first to characterize LA volume, LA reservoir strain, LA conduit strain, and LA booster strain in an ESRD cohort with adjudicated MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al report that LA strain was associated with overall and CV mortality in unadjusted analyses 25 . Papadopoulos et al demonstrated in 79 ESRD patients that LA reservoir strain predicted paroxysmal atrial fibrillation 26 . A recent study of patients with pre‐dialysis chronic kidney disease (CKD) Stages 3/4 by Gan et al showed that LA reservoir strain was a very good predictor (AUC 0.84) for MACE and overall death, and its association with the composite outcome was significant after adjustment for comorbidities and echocardiographic parameters 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the connection between atrial dysfunction and arrhythmic events such as paroxysmal atrial fibrillation, in this group of patients, remains unclear. Papadopoulos et al prospectively evaluated the association between left atrial deformation indices and paroxysmal atrial fibrillation in 79 patients with end stage renal disease and preserved left ventricular systolic function [40]. All patients underwent a baseline comprehensive echocardiography study and were followed for a mean period of 16 ± 5 months.…”
Section: Can Left Atrial Deformation Parameters Predict For Paroxysmamentioning
confidence: 99%